Improving Business Productivity Performance Through Entrepreneurship Training And Entrepreneurship Self - Efficacy - Nanang Adie Setyawan; Bagus Yunianto Wibowo (Jurnal Ekuilnomi, 2023)
This study was conducted to identify entrepreneurial desire and entrepreneurial productivity among Semarang State Polytechnic students after post-covid-19. Respondents in this study were 100 Semarang State Polytechnic students who own businesses. This study used confirmatory factor analysis and maximum likelihood estimation in SEM (Structural Equation Modeling) from the AMOS 24.0 statistical software package (Structural Moment Analysis). The data collection technique used questionnaires with different semantic scales. The results of parameter estimation are in accordance with the hypothesis that entrepreneurial knowledge has a significant effect on business preference with a normalised coefficient estimate of 0.586 and a P-Value of ***, and entrepreneurial training has a positive effect on business preference with a normalised coefficient estimate of 0.470 and a P-Value of *** and entrepreneurial interest has a significant effect on business productivity with a normalised coefficient estimate of 1.007 and a P-Value of ***. From this study, it can be concluded that in the current post- covid-19 context, students who are engaged in the startup world need to increase their education and understanding of entrepreneurship, especially in this time of great need. There must be innovation so that they can survive and develop in a better direction along with the times.